Faktor-Faktor Mempengaruhi Penurunan Pendapatan Petani Padi Tadah Hujan Akibat Pandemi Covid-19 di Desa Sungai Dua Kabupaten Banyuasin - Niasarah, Khalisa; Aryani, Desi; Lifianthi, Lifianthi; Rosana, E.; Malini, Henny (Seminar Nasional Lahan Suboptimal, 2023)
Niasarah, K., Aryani, D., Lifianthi, L., Rosana, E., & Malini, H. (2023). Factors affecting the decreased income of rain-fed rice farmers due to the Covid-19 Pandemic in Sungai Dua Village, Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 683-695).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The existence of Covid-19 pandemic affected many sectors, one of which was the agricultural sector, namely rice farming in Sungai Dua Village. The government's policy of implementing Large-Scale Social Restrictions causes farmers difficulty obtaining subsidized fertilizers, so farmers are forced to reduce the use of fertilizers. During the Covid-19 Pandemic, farmers were forced to buy non-subsidized fertilizers at higher prices, this resulted in increased production costs, thereby reducing farmers' income. The objectives of this study are to: 1) analyze the difference in income of rice farmers before and during the Covid-19 Pandemic; and 2) Analyze the factors that affected the decline in rice farmers' income during the Covid-19 Pandemic. This research was conducted in May until June 2023 in Sungai Dua Village, Rambutan District, Banyuasin Regency. The data collection method used the survey method and sample selection was carried out by simple random sampling method. Analysis was carried out by t test and multiple linear regression. The results showed that there was a significant difference between farmers' income before and during the Covid-19 Pandemic. During the Covid-19 Pandemic, farmers' income fell by around 29.95 percent. Before the Covid-19 Pandemic, rice farmers' income was IDR 16,332,667/la/yr, whereas during the Covid-19 Pandemic, rice farmers' income fell to IDR 11,440,267/la/yr. Factors that had a significant effect on rice farmers' income, namely land area, level of education, fertilizer costs, and labor costs, while the time period dummy has no significant effect on the income of rice farmers.